The nuclear crisis : the arms race, Cold War anxiety, and the German peace movement of the 1980s - Becker-Schaum, Christoph, 1952-; Gassert, Philipp; Klimke, Martin; Mausbach, Wilfried, 1964-; Zepp, Marianne (Protest, culture and society ;, 2016)
"In 1983, more than one million Germans joined together to protest NATO's deployment of nuclear missiles in Europe. International media overflowed with images of marches, rallies, and human chains as protesters blockaded depots and agitated for disarmament. Though they failed to halt the deployment, the episode was a decisive one for German society, revealing deep divisions in the nation's political culture while continuing to mobilize activists. This volume provides a comprehensive survey of the 'Euromissiles' crisis as experienced by its various protagonists, analyzing NATO's diplomatic and military maneuvering and tracing the political, cultural, and moral discourses that surrounded the missiles' deployment in East and West Germany"--Publisher's website